Kinetics and distribution of benzalkonium compounds with different alkyl chain length following intravenous administration in rats. (February 2021) - Kera, Hitomi; Fuke, Chiaki; Usumoto, Yosuke; Nasu, Ayako; Maeda, Kazuho; Mukai, Moe; Sato, Wakana; Tanabe, Momoka; Kuninaka, Hikaru; Ihama, Yoko
Highlights: Kinetics and distribution of the benzalkonium cation (BZK) were analysed. Concentrations of BZK varied in blood and tissue samples. BZK with longer alkyl chains showed lower elimination tendencies. BZK homologue concentrations may help in assessing administration procedures. Abstract: Benzalkonium chloride is widely used in disinfectants. Several toxicological and fatal cases have been reported; however, little is known about its kinetics and distribution. We investigated the kinetic characteristics and distribution of benzalkonium cation (BZK) based on the length of the alkyl chains C12, C14, and C16. Rats were treated intravenously with BZK solution (dose, 13.9 mg/kg) containing equal amounts of the three homologues. Kinetic parameters in the blood were assessed, and BZK distribution in the blood and tissues was examined both in rapid intravenous (IV) and drip intravenous (DIV) administrations. BZK concentrations were analysed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). BZK with longer alkyl chains showed lower elimination tendencies and remained in the blood for a longer duration. Concentrations of BZK were higher in the heart, lung, spleen, and kidney than those in the blood, and lower in the brain and fat. In both the IV and DIV groups, the lung, liver, spleen, and fat samples showed higher concentrations of the longer alkyl chains (BZK-C12 < -C14 < -C16), and the opposite trend was observed in the kidney (BZK-C16 < -C14 < -C12). Only the heart and muscle samples displayed the homologues in ratios comparable to the original administered solutions. Differences between IV and DIV groups could be identified by comparing concentrations of BZK homologues in the heart, lung, spleen, and kidney samples. We found that the kinetics and distribution of BZK were influenced by the alkyl chain length, and analysing each BZK homologues in blood and tissue samples may provide useful information.